2015
DOI: 10.1002/cssc.201500612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Carbonates from Epoxides and Carbon Dioxide by Using Bifunctional One‐Component Phosphorus‐Based Organocatalysts

Abstract: Numerous bifunctional organocatalysts were synthesized and tested for the atom-efficient addition of carbon dioxide and epoxides to produce cyclic carbonates. These catalysts are based on phosphonium salts containing an alcohol moiety in the side chain for substrate activation through hydrogen bonding. In the model reaction, converting 1,2-butylene oxide with CO2 , 19 catalysts were tested to determine structure-activity relationships. In total, 28 epoxides were converted with CO2 to give the respective cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 149 publications
3
92
0
Order By: Relevance
“…While for the shorter ionenes it seems reasonable (based on the observed trends in reactivity) that chlorides are more closely bound to the polymer backbone and thus less readily available for the nucleophilic attack of the epoxide (compared to the bigger and more easily polarizable iodide), it seems that iodides are on the other hand more tightly attached to the polymers in those cases where longer linkers between the ammonium groups are present (thus explaining the different trend in reactivity in these cases). Finally, we tested the use of chloride-based ionenes and adding additional NaI to the reaction mixture (entries [25][26][27][28][29][30] 29,30) which is in accordance to the observations made when using the isolated salts alone (the slightly higher yields may be rationalized by some minor catalytic contribution of the excess NaI). Finally, it was also shown that addition of NaBr has more or less no positive effect (entry 31).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…While for the shorter ionenes it seems reasonable (based on the observed trends in reactivity) that chlorides are more closely bound to the polymer backbone and thus less readily available for the nucleophilic attack of the epoxide (compared to the bigger and more easily polarizable iodide), it seems that iodides are on the other hand more tightly attached to the polymers in those cases where longer linkers between the ammonium groups are present (thus explaining the different trend in reactivity in these cases). Finally, we tested the use of chloride-based ionenes and adding additional NaI to the reaction mixture (entries [25][26][27][28][29][30] 29,30) which is in accordance to the observations made when using the isolated salts alone (the slightly higher yields may be rationalized by some minor catalytic contribution of the excess NaI). Finally, it was also shown that addition of NaBr has more or less no positive effect (entry 31).…”
Section: Resultssupporting
confidence: 69%
“…One transformation that has attracted considerable attention over the last years is the incorporation of CO 2 into epoxides to access cyclic carbonates (for selected rather recent reports with different catalyst systems please see Ref. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]). This transformation is not only interesting because of the importance of the hereby obtained dioxolanes [41,42], but it also provides a powerful approach for the utilization of CO 2 as a simple one carbon-source for organic transformations [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…[9] Numerous catalysts and catalytic systems have been reported for the synthesis of cyclic carbonates from epoxides and CO 2 . [10] However, the development of novel active,t unable and selective catalytic systems is still ac onstant challenge.R ecently,v ery efficient onium salts, [11] ionic liquid [10c, 12] as well as alkalia nd transitionm etal based catalysts have been reported. [10a, 13] Metal systems based on aluminum, sodium and potassium are highly attractive in respect to economy and sustainability,s ince they are usuallyc ost efficient, readily availablea nd nontoxic.…”
Section: Introductionmentioning
confidence: 99%
“…Bifunctional salts 1a and 1b showed much higher activity under these conditions, yielding 3 in 97 and 92%, respectively (entries 3 and 4). 26,27 Further experiments were carried out with 1a …”
Section: ■ Results and Discussionmentioning
confidence: 99%